Pemanfaatan dan Pengolahan Toga (Tanaman Obat Keluarga) Bagi Masyarakat Desa Kerjen Kecamatan Srengat Kabupaten Blitar - Hamidah, Aqnes Dwi Sakti; Wahyu Oktavia, Amidana; Puspitasari, Aulia; Prastiwi, Syahwa Elisa; Marselina, Amelia Putri (Universitas Islam Balitar, 2022)
Community Service Program (KKN) is part of the implementation of the Tri Dharma in Higher Education which introduces and provides students with experience in science, technology and art in community service. It is hoped that students will have concern for the environment so as to build social interaction in the Kerjen Village community. Based on the geographic location of Kerjen Village, most of it is in the form of rice fields, dry land, and public facilities. This village has potential that can be developed, one of which is the large number of plants that can be used as family medicine. Therefore, group 3 strives for human-based health as a concrete manifestation of community participation in health development through TOGA (Family Medicinal Plants). TOGA is a plant that is cultivated by the family because it is efficacious as a traditional medicine. Utilizing TOGA is very important for families to realize the principle of independence in traditional family medicine. The name of this community service activity is